An Analysis toward Marketing System of Rubber (Havea brasiliensis) at Rupat Island of Bengkalis Regency Riau Province - Priyandi '; Cepriadi '; Jum’atri Yusri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The objective of this research is (1) to analyse the margin, profits, and eficiency of Rubber marketing, (2) to find which marketing access is the most profitable for the rubber farmer, (3) to find the relation of the farmers with the marketing institutes or merchants, and (4) to identify the problems faced by the farmers and merchants in rubber marketing. The writer used survey method to collect the data. There were two kinds of respondent in this research taken by using Snaw Ball method; the farmers and the merchants. Those samples consisted of 75 rubber farmers and 12 merchants. The research findings show that the total of margins are Rp 8.000,00/kg at marketing access 1 and Rp 6.500,00/kg in marketing access 2. The efficiencies of marketing are 19% in the marketing access 1, by the profits of Rp 7,733.00/kg obtained by the farmers but 17% in marketing access 2 by the higher profits of Rp 8,907.81/kg. The problems faced by the farmers are getting into debt (33,67%), and the lowest comes from the less available fertilizer. (3.33%).The problems faced by the merchants in marketing access 1 are cost rivalry (50,00%), the destroyed road and the highly water contained (33.34%). The dominant relation of the farmers with the marketing institutes or merchants of rubber at Rupat Island of Bengkalis Regency in the marketing access 1 is as close friends for 9 farmers 15%, while the lowest is as relatives and cousin 6 persons or 6,66%. Finally, in the marketing access 2, the dominant relation of the farmers with the marketing institutes or merchants is unrelated 8 people or 53.33% and the lowest is friends of 2 people or 13,34%. Keywords : Marketing system, Rubber